2016
DOI: 10.1117/12.2236878
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration of titanium oxide nano-coated long-period grating biosensor

Abstract: This work presents an application of sodium hydroxide (NaOH) as an effective method for regeneration of titanium oxide (TiO x ) nano-coated long-period grating (LPG) biosensor. Below 100 nm in thickness TiO x coating was deposited with atomic layer deposition (ALD) method on LPGs for enhancing their refractive index sensitivity up to 2912 nm/RIU in RI range 1.33-1.36 RIU. Next, the sensors were biofunctionalized in order to immobilize receptor (biotin) on their surface and used for selective avidin detection. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Apart from the matter of measurements performed in alkali, also the process of biosensor regeneration that allows for its reusability, may require treatment in high-pH alkaline solutions. An example of this is a regeneration process of specific TiO 2 -overlaid optical fiber biosensors with silane-functionalized active surfaces, for which a solution with a pH 14 was applied [9,10]. Although such high pH value was not optimized and in further experiments it was confirmed that already the pH equal to 9 worked effectively for the sensor regeneration process [11], the alkali treatment still remains necessary.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Apart from the matter of measurements performed in alkali, also the process of biosensor regeneration that allows for its reusability, may require treatment in high-pH alkaline solutions. An example of this is a regeneration process of specific TiO 2 -overlaid optical fiber biosensors with silane-functionalized active surfaces, for which a solution with a pH 14 was applied [9,10]. Although such high pH value was not optimized and in further experiments it was confirmed that already the pH equal to 9 worked effectively for the sensor regeneration process [11], the alkali treatment still remains necessary.…”
Section: Introductionmentioning
confidence: 99%
“…For example Al 2 O 3 and SnO 2 are vulnerable to degradation in alkaline solutions because of their amphoteric chemical nature [24]. Probably for the same reason also TiO 2 layers are not totally safe during prolonged stay in alkali [9,10,25], and they may dissolve very slowly.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation